Reset osmostat (2025)
Introduction: Reset osmostat (RO) is a common syndrome, making up about 30 % of patients with hyponatremia. Objective: Conduct a comprehensive review of osmostat reset, describing its clinical, pathophy siologic, diagnostic, and therapeutic aspects. Methodology: A narrative review was conducted based on the main articles published in the medical literature. Results: Reset osmostat has a low plasma osmolality threshold, which consequently leads to an elevation in antidiuretic hormone at a lower plasma osmolarity, along with normal water load excretion and intact urine diluting ability, while maintaining normal sodium balance. Reset osmostat can be observed in pregnancy, older age, quadriplegia, psychosis, cerebral hemorrhage, encephalitis, dementia, alcoholism, malnutrition, malignancy, and particular infectious diseases. Conclusions: Reset osmostat often resets to normal if it is the consequence of a reversible cli nical setting; however, this normalization might not happen if it is secondary to an irreversible condition. In such cases, treatment is required similar to that of any hyponatremia in order to avoid its negative consequences.